IMPLEMENTASI TEORI ORGANISASI SISTEM DAN KONTINGENSI LEMBAGA PENDIDIKAN ISLAM - Ningsih, Indria (LPPM STAI Muhammadiyah Probolinggo, 2026)
Islamic educational institutions are faced with demand to adapt to changing times, including digitalization and globalization, without sacrificing fundamental Islamic values. A major challenge in Islamic educational management in the modern era is the integration of technology and the availability of resources in accordance with Islamic values. Systems theory is an approach used to understand the complexity of a system by considering the interactions between related components into a holistic whole in its management. The contingency approach or situational approach is a school of management theory that emphasizes specific situations or conditions. Contingency theory emerged as a response to traditional management theory that often ignores variability in organizational situations and contexts. Management success depends on the match between management style and conditions. The implications of both theories, namely Systems Theory and Contingency Theory, can address the challenges and opportunities in Islamic educational management, namely curriculum development, classroom management, improving educational quality, technology integration, strategic planning, and leadership. Meanwhile, opportunities that can be taken are international cooperation, curriculum development, and integrated technology. Overall, these two theories help Islamic educational institutions to become effective, efficient, and adaptive organizations in achieving their goals based on Islamic values ​​amidst the dynamics of the times.